Efficacy of dietary phytosome conjugated cinnamaldehyde supplementation on performance and economics in broilers: Performance and Economics of broilers - A.A. KONDHARE; M.M. KADAM; D.B. BHAISARE; S.V. CHOPADE; A.R. PATIL; G.K. NAGRE (Indian Journal of Poultry Science, 2025)
The present research was designed to assess the efficacy of dietary supplementation of phytosome conjugated cinnamaldehyde essential oil as a feed additive on growth performance and economics of broiler production. A total of 180 commercial broiler chicks (Vencobb-430) at one-day-old age were randomly divided into three groups of four replicates in each (60 chicks/group). The control group received the basal diet, while the other two groups received the basal diet supplemented with Bacitracin Methylene Disalicylate (BMD) @500gm per tonnes and phytosome conjugated cinnamaldehyde essential oil @ 100g/ton of feed, respectively for 42 days. The data obtained demonstrated that, in comparison to other groups, the group that received phytosome conjugated cinnamonaldehyde essential oil at a rate of 100 g/t of feed exhibited significantly (P<0.001) higher live body weight (LBW), body weight gain (BWG), enhanced feed conversion ratio (FCR), and production efficiency index (PEI); furthermore, there was a zero-mortality rate during entire experiment in all the groups. In comparison to supplementing the antibiotic and control diet, which ultimately results in the highest profit per bird, supplementing phytosome conjugated cinnamon aldehyde essential oil yields a higher profit per kg weight. It can be concluded that dietary supplementation of phytosome conjugated cinnamaldehyde essential oils has the potential to improve growth performance of broiler chickens. However, for greater productivity and optimal health, broiler chickens may benefit from consuming 100 g/ton of phytosome conjugated cinnamon aldehyde essential oil as an alternate growth promoter.